Enhancing Multicultural Values Through Pedagogical Approaches in Islamic Education for Senior High Schools - A. Chandra Kusuma Negara; Saihan; Sukamto (South Sulawesi Education Development (SSED), 2025)
This study explores how Islamic Religious Education enhances multicultural values among junipr high school students through thoughtful pedagogical approaches. This research method using a qualitative with case study design, the research delves into how teachers and the school communitywork together to nurture tolerance and respect for diversity. Data were gathered through semi-structured interviews with 17 informants, including 5 ISLAMIC RELIGIOUS EDUCATION teachers, school principal, vice principal for curriculum, and 10 student representatives. These were complemented by classroom observations, deep-interviews, and an analysis of relevant documents, such as lesson plans and student activity reports. The data analysis followed Miles and Huberman's interactive model, focusing on reducing, displaying, and verifying the data to uncover meaningful patterns. To ensure the validity of the findings, triangulation methods were applied, including cross-referencing different sources, member checks with participants, and maintaining detailed research documentation. The results highlight that teachers actively incorporate multicultural values into Islamic Religious Education lessons through group discussions, interfaith dialogues, and culturally inclusive examples. They also create a safe and open classroom atmosphere that encourages students to appreciate diversity and share their unique perspectives. These efforts have led to noticeable changes, including improved interactions across cultural and religious groups, reduced biases, and stronger bonds within the school community.This study emphasizes the essential role of educators in fostering students' understanding of diversity and demonstrates how Islamic Religious Education can become a powerful tool for building a more tolerant and inclusive society.